Gill transcriptomes reveal involvement of cytoskeleton remodeling and immune defense in ammonia stress response in the banana shrimp Fenneropenaeus merguiensis. Issue 71 (December 2017) - Wang, Wei; Yang, Shiping; Wang, Chenggui; Shi, Lili; Guo, Hui; Chan, Siuming
Abstract: The banana shrimp, Fenneropenaeus merguiensis, is an important fishery species in the Indo-West Pacific region. As the shrimp is very sensitive to stressors such as ammonia stress in water, understanding the molecular mechanisms of stress tolerance in F. merguiensis is of pivotal importance for improving its farming performance. In the current study, by using the RNA sequencing platform and comparative transcriptomic analysis, we conducted a comprehensive study on the transcriptomic changes of F. merguiensis in response to ammonia stress. A total of 106, 996 unique transcripts (or unigenes) with an average length of 672 bp and a N50 value of 1164 bp were recovered, and a large number of potential SSR loci in the transcriptome were identified. Totally, 55, 529 transcripts can find significant hits when compared to known sequences in major databases including the nr, nt, SWISSPROT, GO, COG, and KEGG databases. Analysis of differential gene expression between the ammonia-challenged group and the control group revealed that 9190 annotated transcripts were differentially expressed upon ammonia exposure. Among them, 3712 were significantly induced while 5478 of them were repressed. Functional enrichment analysis of these differentially expressed genes further showed that 22 Gene Ontology terms and 62 KEGG pathways were significantly over-represented. Remarkably, many of the genes showing the largest magnitude of expression changes were related to cytoskeleton remodeling and immune response, highlighting the involvement of these biological processes in the ammonia stress response of F. merguiensis . Our study is the first comprehensive investigation on the transcriptomic response to ammonia stress in F. merguiensis . The genes and pathways identified here not only represent valuable genetic resources for development of molecular markers and genetic breeding studies, but open new avenues for studies on the molecular mechanisms of ammonia stress tolerance in penaeid shrimp. Highlights: Transcriptomic changes of F. merguiensis to ammonia stress were examined. A large number of functional genes and associated SSR loci were identified. 22 Gene Ontology terms and 62 KEGG pathways were significantly over-represented. Involvement of cytoskeleton remodeling and immune defense in ammonia stress response were highlighted.